Karakteristik Sains dalam Pemikiran Filosofis Kontemporer (Tinjauan Filsafat Ilmu-Ilmu Keislaman) - Fu`ad Arif Noor (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2019)
Science becomes a furqon/criterion, distinguishing between the quality of the creature, even the quality of the man himself. Science is intended as an appetizer reality, then the name is a reality not only in the form of objects, phenomena, facts, data concrete empirical. So, we need approaches or different methods, and not enough to just rely on the senses, instinct and sheer human rationality. Moreover, basically humans also have the potential tool if used optimally can understand and uncover the whole truth of reality. Philosophy of Science today is better known as a vehicle for interactive dialogue between philosophy and science. Science is